Safety of Overlapping Inpatient Orthopaedic Surgery: A Multicenter Study - Dy, Christopher J. (J Bone Joint Surg Am, 2018)
BACKGROUND: Although overlapping surgery is used to maximize efficiency, more empirical data are needed to guide patient safety. We conducted a retrospective cohort study to evaluate the safety of overlapping inpatient orthopaedic surgery, as judged by the occurrence of perioperative complications. METHODS: All inpatient orthopaedic surgical procedures performed at 5 academic institutions from January 1, 2015, to December 31, 2015, were included. Overlapping surgery was defined as 2 skin incisions open simultaneously for 1 surgeon. In comparing patients who underwent overlapping surgery with those who underwent non-overlapping surgery, the primary outcome was the occurrence of a perioperative complication within 30 days of the surgical procedure, and secondary outcomes included all-cause 30-day readmission, length of stay, and mortality. To determine if there was an association between overlapping surgery and a perioperative complication, we tested for non-inferiority of overlapping surgery, assuming a null hypothesis of an increased risk of 50%. We used an inverse probability of treatment weighted regression model adjusted for institution, procedure type, demographic characteristics (age, sex, race, comorbidities), admission type, admission severity of illness, and clustering by surgeon. RESULTS: Among 14,135 cases, the frequency of overlapping surgery was 40%. The frequencies of perioperative complications were 1% in the overlapping surgery group and 2% in the non-overlapping surgery group. The overlapping surgery group was non-inferior to the non-overlapping surgery group (odds ratio [OR], 0.61 [90% confidence interval (CI), 0.45 to 0.83]; p < 0.001), with reduced odds of perioperative complications (OR, 0.61 [95% CI, 0.43 to 0.88]; p = 0.009). For secondary outcomes, there was a significantly lower chance of all-cause 30-day readmission in the overlapping surgery group (OR, 0.67 [95% CI, 0.52 to 0.87]; p = 0.003) and shorter length of stay (e(β), 0.94 [95% CI, 0.89 to 0.99]; p = 0.012). There was no difference in mortality. CONCLUSIONS: Our results suggest that overlapping inpatient orthopaedic surgery does not introduce additional perioperative risk for the complications that we evaluated. The suitability of this practice should be determined by individual surgeons on a case-by-case basis with appropriate informed consent. LEVEL OF EVIDENCE: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.